Lateral Antebrachial Cutaneous Nerve injury induced by phlebotomy - Rayegani, S Mansoor; Azadi, Arezoo (Journal of Brachial Plexus and Peripheral Nerve Injury, 2007)
Background Phlebotomy is one of the routine procedures done in medical labs daily.Case presentation A 52 yr woman noted shooting pain and dysesthesia over her right side anterolateral aspect of forearm, clinical examination and electrodiagnostic studies showed severe involvement of right side lateral antebrachial cutaneous nerve.Conclusion Phlebotomy around lateral aspect of antecubital fossa may cause lateral antebrachial cutaneous nerve injury, electrodiagnostic studies are needed for definite diagnosis.